Identificación y evaluación de riesgos laborales para la elaboración de un manual de trabajo seguro en el laboratorio de ingeniería agronómica de CAREN de la Universidad Técnica de Cotopaxi en el periodo 2017 - Chicas Salazar, Ricardo Gabriel (2017)
The research project was carried out by means of the identification, evaluation, control and monitoring of the risk factors for occupational safety and health as part of the Andean Instrument on Safety and Health at Work D584 and its Regulation 957 in the Resolution of the Council of the IESS CD513. The deficit of the technical management in the labor risks causes actions and sub-standard conditions in the work environment. Reference is taken in the descriptive method based on the research contribution, the collection of data within the environment through the use of interview, check list, observation, with the result of a situation analysis. In the Laboratory of Agricultural Engineering from the Technical University of Cotopaxi Campus Salache, aims to propose preventive security measures before the risk levels in the Occupational Safety and Health for the lab users, due to the fact that the staff should conduct their activities in a safe working environment and comfortable….